Brassinosteroid/Sterol Synthesis and Plant Growth as Affected by lka and lkb Mutations of Pea - Nomura, Takahito (American Society of Plant Physiologists, 1999)
The dwarf pea (Pisum sativum) mutants lka and lkb are brassinosteroid (BR) insensitive and deficient, respectively. The dwarf phenotype of the lkb mutant was rescued to wild type by exogenous application of brassinolide and its biosynthetic precursors. Gas chromatography-mass spectrometry analysis of the endogenous sterols in this mutant revealed that it accumulates 24-methylenecholesterol and isofucosterol but is deficient in their hydrogenated products, campesterol and sitosterol. Feeding experiments using (2)H-labeled 24-methylenecholesterol indicated that the lkb mutant is unable to isomerize and/or reduce the Δ(24(28)) double bond. Dwarfism of the lkb mutant is, therefore, due to BR deficiency caused by blocked synthesis of campesterol from 24-methylenecholesterol. The lkb mutation also disrupted sterol composition of the membranes, which, in contrast to those of the wild type, contained isofucosterol as the major sterol and lacked stigmasterol. The lka mutant was not BR deficient, because it accumulated castasterone. Like some gibberellin-insensitive dwarf mutants, overproduction of castasterone in the lka mutant may be ascribed to the lack of a feedback control mechanism due to impaired perception/signal transduction of BRs. The possibility that castasterone is a biologically active BR is discussed.